An examination of major works for wind band and chamber ensemble: Flight by Claude T. Smith, Baron Cimetiére’s mambo by Donald Grantham, and Suite persane by André Caplet - Sullivan, Patrick James (Kansas State University, 2013)
The following report is a comprehensive analysis of two works for wind band and one work for small chamber ensemble, prepared by Patrick Sullivan. The report was completed in addition to a Graduate Conducting Recital, taking place on Sunday, March 10, 2013 at 3:00pm. The concert featured the Kansas State University Wind Ensemble and took place on the Kansas State University Campus in McCain Auditorium, the conductors were Andrew Feyes and Patrick Sullivan. Audio and video recordings of the conducted performance can be found within the K-State Research Exchange database. The following report includes three comprehensive Unit Studies or Teacher Research Guides found in the Teaching Music Through Performance in Band book series. The report also includes three Tracz Analysis Grids, newly published in The Art of Interpretation of Band Music. The examined pieces are as follows. Full band works, Flight by Claude T. Smith and Baron Cimetiére’s Mambo by Donald Grantham. A chamber work for double woodwind quintet, Suite Persane by André Caplet.
Keywords: Conducting; Analysis; Claude Smith; Donald Grantham; Andre Caplet; Music (0413); Musical Performances (0943); Music Education (0522)